Humanized mouse model: Hematopoietic stemcell transplantation and tracking using short tandem repeat technology. Issue 3 (11th June 2020) - Walcher, Lia; Hilger, Nadja; Wege, Anja K.; Lange, Franziska; Tretbar, U. Sandy; Blaudszun, André‐René; Fricke, Stephan
Abstract: Introduction: Models of mice carrying a human immune system, so‐called humanized mice, are used increasingly as preclinical models to bridge the gap between model organisms and human beings. Challenges of the humanized mouse model include finding suitable sources for human hematopoietic stem cells (HSC) and reaching sufficient engraftment of these cells in immunocompromised mice. Methods: In this study, we compared the use of CD34 + HSC from cord blood (CB) vs HSC from adult mobilized peripheral blood. Furthermore, we developed a simple and highly specific test for donor identification in humanized mice by applying the detection method of short tandem repeats (STR). Results: It was found that, in vitro, CB‐derived and adult HSC show comparable purity, viability, and differentiation potential in colony‐forming unit assays. However, in vivo, CB‐derived HSC engrafted to a significantly higher extent in NOD.Cg‐Prkdc scid IL2rγ tm1Wjl /SzJ (NSG) mice than adult HSC. Increasing the cell dose of adult HSC or using fresh cells without cryopreservation did not improve the engraftment rate. Interestingly, when using adult HSC, the percentage of human cells in the bone marrow was significantly higher than that in the peripheral blood. Using the STR‐based test, we were able to identify and distinguish human cells from different donors in humanized mice and in a humanized allogeneic transplantation model. Conclusion: From these findings, we conclude that adult mobilized HSC are less suitable for generating a humanized immune system in mice than CB‐derived cells. Abstract : In this study, the authors present new insights into the humanized immune system mouse model. CB‐derived hematopoietic stem cells (HSC) are shown to engraft in NSG mice to a significantly higher extent than adult HSC. Furthermore, a simple and highly specific test method for the tracking of the human donor(s) in humanized mice is presented.